Efecto de la fuente de nitrógeno en la producción de la enzima manganeso peroxidasa producida por pleurotus ostreatus y determinación de sus constantes cinéticas (2019)
The use of lignocellulosic residues for the production of molecules of interest, such as sugars and biofuels, also includes the synthesis of enzymatic complexes composed by oxidases capable of degrading aromatic and phenolic structures of a pollution nature in certain cases. This study evaluated the production of manganese peroxidase (MnP) in a liquid fermentation submerged by pleurotus ostreatus using as substrate a forage grass. The highest levels of enzymatic activity (528.54 U/L) were obtained after twelve days of incubation and having as a nitrogen source peptone, at a carbon/nitrogen ratio equal to 10. In the cases in which the fermentation was supplemented with inorganic nitrogen sources, the enzymatic activity was lower.